Efficacy and safety of nintedanib in patients with non-small cell lung cancer, and novel insights in radiation-induced lung toxicity - Yan, Shu; Xue, Shuyu; Wang, Tiantian; Gao, Ruihang; Zeng, Hanqiao; Wang, Qianmeng; Jia, Xiaojing (Frontiers in Oncology, 2023)
Nintedanib is a tyrosine kinase inhibitor of fibroblast growth factor-, vascular endothelial growth factor-, and platelet-derived growth factor receptors. These three receptors promote new blood vessel formation and maintenance, which is essential for tumor growth and spread. Several trials have shown that nintedanib plays a substantial role in treating patients with non-small cell lung cancer (NSCLC) and idiopathic pulmonary fibrosis. Recently, several clinical trials of nintedanib to treat NSCLC have been reported. In this review, we focus on our current understanding of nintedanib treatment for advanced NSCLC patients and summarize the literature on using nintedanib in radiation-induced lung toxicity and the efficacy and tolerability of nintedanib.